Unemployment Insurance and Male Unemployment Duration in Canada - Ham, John C.; Rea, Samuel A. (Journal of Labor Economics, 1987)
A model of unemployment duration is estimated with weekly micro data on Canadian men. Ent itlement provisions in the unemployment insurance program and demand conditions are found to have a significant effect on the probability of leaving unemployment. The probability of a worker leaving unemploy ment declines with the duration of unemployment, holding unemployment insurance entitlement constant. When entitlement is allowed to vary, the probability of leaving first falls and then generally rises with unemployment duration. These results are robust with respect to allo wing for person-specific unobserved heterogeneity and alternative spe cifications of duration dependence. Copyright 1987 by University of Chicago Press.